"Ambiguous, Confusing, and Not Delivering Enough Housing": What Negotiations Theory Can Teach Us About Voluntary Affordable Housing Agreements. Issue 4 (2nd October 2021) - Raynor, Katrina; Palm, Matthew; Warren-Myers, Georgia
Abstract: Problem, research strategy, and findings: Responsibility for affordable housing delivery is increasingly being delivered through collaborations between private, nonprofit, and state actors and operationalized through voluntary negotiations. Negotiation theory provides a lens for understanding why outcomes are often limited by highlighting the impact of stakeholder interests, the potential for mutual gains, trust between negotiating partners, and access to information. We surveyed 148 housing stakeholders in the state of Victoria (Australia) shortly after the passage of legislation that supported the negotiation of voluntary affordable housing agreements. We found that stakeholders share a belief in the necessity of affordable housing. However, the current institutional context often precludes opportunities for mutual gain because there is little incentive to engage in negotiations, provision of sufficient incentives is problematic, and contributions are difficult to enforce. We found large discrepancies in levels of training in development feasibility across sectors and low trust between negotiation participants. We argue that these factors are likely to reduce the efficiency and effectiveness of voluntary affordable housing negotiations in Victoria and other jurisdictions with weak institutional arrangements for affordable housing negotiations. Takeaway for practice: Across sectors, respondents prefer mandatory rather than voluntary affordable housing provisions. Voluntary affordable housing negotiations are unlikely to be effective without institutional scaffolding to ensure that negotiations result in mutual gains for stakeholders. Planners should pair the introduction of voluntary affordable housing negotiations with training resources for the stakeholders who will participate in negotiations as well as mechanisms for enforcing negotiated agreements.